The Alkaline Diet and the Warburg Effect - Hassan Bahrami; Ted Greiner (World Nutrition, 2021)
The changing diets accompanying our modern life style have increased the content of foods that form acidic metabolic waste residues in the body. Wastes from these metabolic processes are released into the interstitial fluids and the blood, slightly changing their pH temporarily. This link may in turn have an impact on the incidence of non-communicable diseases (NCDs).